Future Changes in the Asian‐Australian Monsoon System With 1.5°C and 2°C Rise in Temperature. Issue 2 (25th January 2021) - Wang, Hui; Ji, Zhenming; Zhu, Xian; Lin, Lei; Dong, Wenjie
Abstract: Future changes in the Asian‐Australian monsoon (AAM) and its submonsoons are investigated based on low‐emission scenario simulations using the Community Earth System Model, which are under the 1.5°C and 2.0°C warming targets proposed by the Paris Agreement. Changes in the AAM system are projected by the end of the 21st century: (1) The AAM summer precipitation at the 1.5°C warming target will increase by 4.1% because of the strong enhancement of the Asian summer monsoon (ASM). The maximum is 12.4% in the East Asian summer monsoon (EASM) region. The summer monsoon precipitation of AAM system will be further enhanced by 0.4%–3.1% in the 2°C warming target. Indochina Peninsula and China will be influenced by the significant increase of land monsoon precipitation. (2) The summer precipitation of AAM and ASM submonsoons will increase near‐linearly with the local surface temperature warming. Precipitation budget diagnosis shows that the increase in precipitation of AAM and its submonsoons, except for EASM, is only contributed by enhanced moisture. However, the effects of thermodynamic and dynamic contributions are equally essential for EASM. (3) The AAM domain will change insignificantly at both 1.5°C and 2°C warming targets. (4) The AAM‐El Niño‐Southern Oscillation relationship will slightly change at 1.5°C warming targets but will be enhanced at 2.0°C warming targets. This work shows that compared to 1.5°C warming targets, societies will be influenced by higher monsoon precipitation, especially in EASM region, but these changes can be more easily predicted with 2°C temperature rise. Key Points: The Asian‐Australian monsoon (AAM) summer precipitation will increase at the 1.5°C and 2°C warming targets, but differences exist between submonsoon regions The dynamic contribution favors the precipitation increase in East Asian summer monsoon, but offsets the precipitation change over other submonsoon regions The Asian‐Australian monsoon ‐ El Niño‐Southern Oscillation relationship will be enhanced at the 2°C warming target